Stem pitting disease caused by citrus tristeza virus - Amit Levy; Peggy Sieburth; Ozgur Batuman (EDIS, 2022)
Stem pitting disease caused mostly by VT isolates of citrus tristeza virus (CTV) can be a very serious disease on citrus types and varieties that are widely grown in Florida, such as sweet orange and grapefruit. Once a tree is infected with CTV stem pitting, the long-term economic effects to the grower may be even worse than those from decline isolates of CTV. VT isolates that induce mild to moderate stem pitting in grapefruit and sweet orange were previously reported from Florida and are still present here today. Fortunately, CTV isolates causing severe stem pitting have not been detected in Florida yet. It is important to continue to studying CTV and its impact in Florida in order to keep severe stem pitting out of the state.